PENERAPAN PEMBELAJARAN BLENDED LEARNING PADA MAHASISWA SEMETER 6 MATA KULIAH PPLK 1 PROGRAM STUDI PPKN - Lina Marlina; Muhammad Asmawi; Alamsyah Basri (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2021)
ABSTRACT Blended learning is applied to the PPLK 1 course for 6th-semester students by the lecturer in the PPLK 1 course which must be given to students of the PPLK study program and as a prerequisite before they are sent to school to implement PPLK 2 in the PPLK 1 course. also as a type of lecture in the form of Micro Teaching which will create prospective teachers of the Civics Study Program to become professional educators in the field of teacher training. The purpose of research in the form of a blended learning process is to train and prepare students as professional teacher candidates using a blended learning-based learning process, namely face-to-face learning and e-learning. The form of research used in this research is qualitative research with a descriptive method. Based on the results of the study, it can be concluded that by applying blended learning to students in semester 6 of PPLK 1 courses, the PPKn Study Program, the learning process can be said to be successful and give a positive response to blended learning. The results of this study make students not feel that the learning process is monotonous and good. Supporting lecturers and students get good results from the PPLK 1 course learning process and gain experience of learning models using two activities, namely face-to-face learning and e-learning.